Acculturation in Culture Site Kelenteng Cu An Kiong - Lasem Viewed from Architectural and Decoration Angle - Randy Indra Pradhana; Ananda Dianti; Agnes Paulina (Bina Nusantara University, 2020)
The entry of the influence of various foreign cultures in Indonesia can be seen in various aspects of cultural products. One of the things we can see is that there are a lot of cultural sites built in various regions that are influenced by foreign cultures. Cu An Kiong Temple in Lasem, Central Java is one of them. The research proposed in this proposal has a specific target to examine more deeply the influence of Chinese culture which is applied in the architectural style of the Cu An Kiong temple cultural site, with a long-term goal of cultural preservation in Indonesia which has experienced acculturation with local local culture. The research method was carried out by direct observation at the location, visual documentation and making notes about the architectural style used, and using literature